2003
DOI: 10.1161/01.cir.0000100723.50363.2c
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison Between Stenting and Off-Pump Bypass Surgery in Patients Referred for Angioplasty

Abstract: Background-Stenting improves cardiac outcome in comparison with balloon angioplasty. Compared with conventional surgery, off-pump bypass surgery on the beating heart without cardiopulmonary bypass may reduce morbidity, hospital stay, and costs. The purpose, therefore, was to compare cardiac outcome, quality of life, and cost-effectiveness 1 year after stenting and after off-pump surgery. Methods and Results-Patients referred for angioplasty (nϭ280) were randomly assigned to stenting (nϭ138) or off-pump bypass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 31 publications
1
27
1
4
Order By: Relevance
“…After title and abstract review, 75 citations were examined in detail; however, 48 were excluded because they failed to meet the specified inclusion criteria. A total of 27 eligible trials were identified for inclusion, but 17 had to be excluded for the following reasons: data no longer available (n=3) 17-19 ; insufficient data to calculate eGFR (n=7) 20-26 unable to contact the investigators despite multiple attempts (n=3) 27-29 ; investigators unable (n=2) 30, 31 or unwilling (n=2) 32, 33 to share data.…”
Section: Resultsmentioning
confidence: 99%
“…After title and abstract review, 75 citations were examined in detail; however, 48 were excluded because they failed to meet the specified inclusion criteria. A total of 27 eligible trials were identified for inclusion, but 17 had to be excluded for the following reasons: data no longer available (n=3) 17-19 ; insufficient data to calculate eGFR (n=7) 20-26 unable to contact the investigators despite multiple attempts (n=3) 27-29 ; investigators unable (n=2) 30, 31 or unwilling (n=2) 32, 33 to share data.…”
Section: Resultsmentioning
confidence: 99%
“…The discussion about potential shortcomings of CABG as compared to PCI was fueled after the first large industry‐funded trial3 found significantly higher rates of major adverse cardiac and cerebrovascular events in the PCI group (17.8% versus 12.4% for CABG; P =0.002), in large part because of an increased rate of repeat revascularization (13.5% versus 5.9%); however, at 12 months, strokes were 4‐fold more likely to occur with CABG (2.2% versus 0.6% with PCI; P =0.003). None of the following studies comparing PCI with OPCAB38, 39, 40, 41 were powered for stroke, and none reports the extent of “no‐touch” technique in the CABG group. Conversely, one recent trial assessing midterm outcomes of 438 patients randomly assigned to the PCI with everolimus eluting stents and 442 randomly assigned to the CABG group42 found no difference in the risk of stroke between the 2 groups: hazard ratio 0.86 (0.39–1.93); P =0.72.…”
Section: Discussionmentioning
confidence: 99%
“…Полученные результаты в целом согласуются с ранее проведенными исследованиями, сравнивающими АКШ и ЧКВ у больных ишемической болезнью сердца [16][17][18][19]. Особенностью оказания хирургической реваскуляризации методом АКШ у больных ОКС с многососудистым поражением является необходимость проведения агрессивной интенсивной терапии для компенсации недостаточности кровообращения и стабилизации нестабильной стенокардии: игнорирование вышеназванных действий ухудшает результаты операций АКШ [19].…”
Section: оригинальные исследованияunclassified